1996
DOI: 10.1172/jci118464
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic depletion of CD4+ T cells in idiopathic CD4+ T lymphocytopenia.

Abstract: Progressive loss of CD4 ؉ T lymphocytes, accompanied by opportunistic infections characteristic of the acquired immune deficiency syndrome, has been reported in the absence of any known etiology. The pathogenesis of this syndrome, a subset of idiopathic CD4 ؉ T lymphocytopenia (ICL), is uncertain. We report that CD4 ؉ T cells from seven of eight ICL patients underwent accelerated programmed cell death, a process facilitated by T cell receptor cross-linking. Apoptosis was associated with enhanced expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 51 publications
6
64
0
1
Order By: Relevance
“…The requirement for T-cell activation seems to be a common feature of monocyte-dependent apoptosis mediated by Fas-FasL interaction (30,34,35). Laurence et al suggested that patients with ICL linked to clinical immune suppression have evidence for accelerated T cell apoptosis in vitro (22) and Roger et al reported an ICL case in which CD4 positive T lymphopenia was correlated with an overexpression of CD95 (Fas receptor) together with spontaneous and Fas-induced apoptosis (24). The result of the present patient was compatible with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for T-cell activation seems to be a common feature of monocyte-dependent apoptosis mediated by Fas-FasL interaction (30,34,35). Laurence et al suggested that patients with ICL linked to clinical immune suppression have evidence for accelerated T cell apoptosis in vitro (22) and Roger et al reported an ICL case in which CD4 positive T lymphopenia was correlated with an overexpression of CD95 (Fas receptor) together with spontaneous and Fas-induced apoptosis (24). The result of the present patient was compatible with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…P-values (log-rank test) corresponding to the differences between the growth curves of CPT-11 treated HT29 and HT29A3 tumours, are indicated Mice were treated with CPT-11 at low dose (A) (10 mg kg -1 at 4-day intervals × 4) or high dose (B) (40 mg kg -1 at 4-day intervals × 6). P-values (log-rank test) corresponding to the differences between the growth curves of CPT-11 treated LoVo and X17LoVo tumours, are indicated 270-290 of the fas-apo-1 receptor gene coding sequence (Laurence et al, 1996)) fasR-2: AS 5′-CCT TGG TTT TCC TTT CTG TGC-3′ (bases 797-817 of the fas-apo-1 receptor gene coding sequence (Laurence et al, 1996)) hprt-1: S 5′-CAA CAG GGG ACA TAA AAG TAA T-3′ (bases 414-435 of the hprt-gene coding sequence) hprt-2: AS 5′-AGT CCG TCA TAT TAG GTT TCT-3′ (bases 534-554 of the hprt-gene coding sequence).…”
Section: Pcr Primersmentioning
confidence: 99%
“…[13][14][15][16] In the latter scenario, lymphopenia resulting from up-regulated in vivo apoptosis is the clinical finding in human immunodeficiencies, such as idiopathic CD4 ϩ T lymphocytopenia, and it correlates with increased levels of CD95 and CD95L, a finding also observed in patients with CD8 ϩ T lymphopenia. 17 Lymphocytopenias found in adults could also result from adenosine deaminase deficiency. 18 Other factors implicated in different forms of apoptosis are reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%